O sopostavitelʺ noi stilistike russkogo i bolgarskogo âzykov - Avramova, Valentina (Stylistyka, 2021)
The paper discusses comparative stylistics which consists of two parts. Part one deals with comparative stylistics of the resources of the Russian and Bulgarian language. Part two analyses the functional styles of the Russian and the Bulgarian language. The stylistic resources of the Russian and the Bulgarian language are to be investigated in terms of functional and stylistic fields.